Der Weg zum Garten in Nain im Mai : [1908] - Lenz, Berthold, 1873-1960. (2001)
Black and white photograph of the path to the garden in Nain. The photogaph was taken in May, 1908. Black and white photograph of the path to the garden in Nain. The photogaph was taken in May, 1908.